STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN KERIPIK SINGKONG PADA UKM REJEKI MANGOKO DI KELURAHAN SULAMADAHA - Tuara, Narilah A (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2023)
The problem in this research is to find out what the marketing strategy is for selling cassava chips to the Rejeki Mangoko UKM in Sulamadaha sub-district. Marketing of products in the cassava chips business in UKM Rejeki Mangoko, Sulamadaha sub-district is still very minimal so that the products being marketed are not well known to the wider community. The aim of the research is to find out the marketing strategy for selling cassava chips at Rejeki Mangoko UKM in Sulamadaha Village. This research method uses a qualitative approach with descriptive methods. The respondents for this research are owners, employees and customers. Data collection techniques were interviews, observation and documentation. Data analysis used interactive analysis. The results of the research show that the chips marketing strategy with cassava chips managers carries out capital management, carries out management of raw materials for cassava chips, carries out production management of cassava chips, and carries out marketing management, the business management is carried out with significant and complementary management. The role of this marketing strategy can have an impact on the management of cassava chips on home industries in Sulamadaha Village, it has a positive impact, namely the management of cassava chips can create jobs, the business of managing cassava chips can reduce the number of unemployed and the management of cassava chips can increase people's income in Sulamadaha district